Cumulate olivine: A novel host for heavy rare earth element mineralization - Brandt, Sönke; Faßbender, Marc Lorin; Klemd, Reiner; Macauley, Chandra; Felfer, Peter; Haase, Karsten (Geology, 2020)

Formation of the Vergenoeg F-Fe-REE deposit (South Africa) by accumulation from a ferroan silicic magma - Brandt, Sönke; Klemd, Reiner; Haase, Karsten; Faßbender, Marc Lorin; Vennemann, Torsten (Journal of Petrology, 2020)

Geochronological evidence for Archaean and Palaeoproterozoic polymetamorphism in the Central Zone of the Limpopo Belt, South Africa - Kröner, Alfred; Brandl, Guenther; Brandt, Sönke; Klemd, Reiner; Xie, Hangqiang (Precambrian Research, 2018)
The Central Zone of Limpopo Belt is a polymetamorphic and complexly deformed Precambrian terrane whose tectonic evolution is still uncertain because details on the timing of its evolution are not well established. We report zircon ages for newly discovered rocks in the Central Zone which document three distinct high-grade tectono-metamorphic events at 3.22, 2.62 and 2.02 Ga. The youngest of these has been well established, but the older two events were so far largely based only on rare zircon overgrowth rims. Most of our samples were collected from a large enclave in the 2.61 Ga Bulai pluton and constitute a strongly deformed, brecciated high-grade assemblage of supracrustal rocks, meta-anorthosite and granitoid gneisses, some of which are most likely equivalents of the pre-3.33 Ga Beit Bridge Complex. Magmatic zircon ages of 3.34–3.33 Ga for anorthositic and tonalitic gneisses in the enclave breccia support this correlation. Ca. 3.22 Ga metamorphic zircons, possibly reflecting the D1/M1 event, were only found in one felsic granulite sample, and their regional significance remains uncertain. Abundant metamorphic zircons grew at ca. 2.62 Ga under granulite-facies conditions (D2/M2), and some of these experienced variable degrees of recrystallization and/or Pb-loss during the third granulite-facies event at ca. 2.0 Ga (D3/M3). Rocks outside the Bulai enclave contain abundant newly-formed ca. 2.02 Ga metamorphic zircons but only rarely preserve evidence for the ca. 2.62 Ga event since these late Archaean zircons show strong recrystallization and/or Pb-loss at ca. 2.0 Ga. We suggest that the Bulai pluton “protected” the rocks inside the enclave from severe overprinting at ca. 2.0 Ga because these rocks remained dry, whereas the assemblages outside the Bulai pluton experienced fluid-assisted metamorphic overprinting at ca. 2.0 Ga. Our new data sugggest that the tectonic evolution of the Central Zone was more complex than previously thought. We favour a scenario where collision involving the Limpopo Belt occurred in the Neoarchaean, whereas the high-grade Palaeoproterozoic event was most likely intracontinental and records far-field effects of plate movements elsewhere. The tectonic setting controlling the early Archaean D1/M1 event remains unknown, largely because of insufficient data and extensive overprinting during later time

Magmatic evolution of the Schiel Alkaline Complex, Bushveld large igneous province, South Africa - Höß, Alica; Klemd, Reiner; Bolhar, Robert; Haase, Karsten; Ramos, Joshua; Geiger, Elena; Brandt, Sönke; Graupner, Torsten (Lithos, 2024)
The Paleoproterozoic Schiel Alkaline Complex (SAC) in the Limpopo Belt is a composite pluton that coevally formed with the layered intrusion of the Bushveld large igneous province. The SAC is mainly composed of alkaline felsic rocks, pyroxenite, gabbro, syenodiorite/−gabbro, and minor carbonatite and gabbroic dikes. Here we present a new geochemical, geochronological, and isotopic study of the felsic and (ultra)mafic rock suites of the western SAC. The whole rock Sm[sbnd]Nd isotope study of the felsic rocks revealed εNd2059 Ma values between −6.5 and − 3.8, while those of the syenodiorite/−gabbros and gabbros vary from −7.9 to −8.8, and − 4.3 to +1.1, respectively. The pyroxenites have εNd2059 Ma values of +7.4 to +2.7. The Lu[sbnd]Hf isotope study displays εHf2059 Ma values of −15.9 to −9.0 for the syenites, alkali granites and syenodiorite/−gabbros, and significantly higher εHf2059 Ma of −3.1 to +3.4 for the gabbros. LA-SF-ICPMS U[sbnd]Pb zircon dating yields 2079 ± 10 Ma and 2088 ± 30 Ma for the syenodiorite/−gabbros, and 2086 ± 51 Ma and 2107 ± 30 Ma for the gabbros. In conjunction with published data from the eastern SAC, we propose a close petrogenetic link between the mafic and felsic rocks of the SAC. The positive εNd and εHf values of the pyroxenite and gabbro favor a depleted mantle source, while variable εNd and εHf values, and trace element ratios of the gabbros are ascribed to crustal contamination during magma ascent. The felsic rocks, however, mainly formed by fractional crystallization from the gabbros as revealed by major and trace element correlation trends, isotopic data and thermodynamic modelling.
CRIS-Team Scopus Importer:2024-01-05
Keywords: Alkaline complex; Bushveld LIP; Crustal assimilation; Fractional crystallization; Nd-Hf isotope compositions; Rare earth elements

Metamorphic petrology of a high-T/low-P granulite terrane (Damara belt, Namibia) – Constraints from pseudosection modelling and high-precision Lu–Hf garnet-whole rock dating - Jung, Stefan; Brandt, Sönke; Bast, Rebecca; Scherer, Erik E.; Berndt, Jasper (Journal of Metamorphic Geology, 2019)
Migmatites comprise a minor volume of the high-grade part of the Damara orogen of Namibia that is dominated by granite complexes and intercalated metasedimentary units. Migmatites of the Southern Central Zone of the Damara orogen consist of melanosomes with garnet+cordierite+biotite+K-feldspar, and leucosomes, which are sometimes garnet- and cordierite-bearing. Field evidence, petrographic observations, and pseudosection modelling suggest that, in contrast to other areas where intrusion of granitic magmas is more important, in situ partial melting of metasedimentary units was the main migmatite generation processes. Pseudosection modelling and thermobarometric calculations consistently indicate that the peak-metamorphic grade throughout the area is in the granulite facies ( 5 kbar at 800°C). Cordierite coronas around garnet suggest some decompression from peak-metamorphic conditions and rare andalusite records late, near-isobaric cooling to <650°C at low pressures of 3 kbar. The inferred clockwise P–T path is consistent with minor crustal thickening through continent–continent collision followed by limited post-collisional exhumation and suggests that the granulite facies terrane of the Southern Central Zone of the Damara orogen formed initially in a metamorphic field gradient of 35–40°C/km at medium pressures. New high-precision Lu–Hf garnet-whole rock dates are 530 ± 13 Ma, 522.0 ± 0.8 Ma, 520.8 ± 3.6 Ma, and 500.3 ± 4.3 Ma for the migmatites that record temperatures of 800°C. This indicates that high-grade metamorphism lasted for c. 20–30 Ma, which is compatible with previous estimates using Sm–Nd garnet-whole rock systematics. In previous studies on Damara orogen migmatites where both Sm–Nd and Lu–Hf chronometers have been applied, the dates (c. 520–510 Ma) agree within their small uncertainties (0.6–0.8% for Sm–Nd and 0.1–0.2% for Lu–Hf). This implies rapid cooling after high-grade conditions and, by implication, rapid exhumation at that time. The cause of the high geothermal gradient inferred from the metamorphic conditions is unknown but likely requires some extra heat that was probably added by intrusion of magmas from the lithospheric mantle, i.e., syenites that have been recently re-dated at c. 545 Ma. Some granites derived from the lower crust at c. 545 Ma are the outcome rather than the cause of high-T metamorphism. In addition, high contents of heat-producing elements K, Th, and U may have raised peak temperatures by 150–200°C at the base of the crust, resulting in the widespread melting of fertile crustal rocks. The continuous gradation from centimetre-scale leucosomes to decametre-scale leucogranite sheets within the high-grade metamorphic zone suggests that leucosome lenses coalesced to form larger bodies of anatectic leucogranites, thereby documenting a link between high-grade regional metamorphism and Pan-African magmatism. In view of the close association of the studied high-T migmatites with hundreds of synmetamorphic high-T granites that invaded the terrane as metre- to decametre-wide sills and dykes, we postulate that crystallization of felsic lower crustal magma is, at least partly, responsible for heat supply. Late-stage isobaric cooling of these granites may explain the occurrence of andalusite in some samples.
CRIS-Team Scopus Importer:2019-10-11
Keywords: Damara orogen; granulite facies metamorphism; Lu–Hf garnet dating; migmatites; Namibia

Metamorphic Response to Alpine Thrusting of a Crustal-scale Basement Nappe in Southern Calabria (Italy) - Brandt, Sönke; Schenk, V. (Journal of Petrology, 2020)
Structural, geophysical and age data indicate that the tilted cross-section of the Variscan continental crust exposed in the Serre of southern Calabria forms the uppermost Alpine nappe ('Serre nappe') of three Variscan basement slices derived from the southern European margin. This Alpine nappe stack is a fragment of the western Mediterranean Alps and rests now, after Miocene emplacement, on top of the Apennine carbonate platform. We report for the first time a P-T path for prograde Alpine metamorphism, which is restricted to the two lower nappes (Castagna and Bagni nappes) that are squeezed between cooler tectonic units, the Serre nappe above and the Apennine platform below. Therefore, we attribute their metamorphism to tectonic loading and concomitant shear heating during Eocene south-directed overthrusting of the crustal-scale Serre nappe. In the underlying Castagna nappe, Alpine metamorphism is only locally recorded, mainly by new growth of garnet, forming at the expense of retrogressed Variscan biotite dated at 43 Ma. The local existence of Alpine besides relict Variscan mineral assemblages in the strongly but heterogeneously overprinted rocks allows for characterization of metamorphic evolutions during both the Alpine and Variscan orogeneses in the former intermediate level of the Variscan crust of Calabria. The metamorphic evolutions have been reconstructed through P-T pseudosection modelling for Al-rich metasediments. In the Castagna nappe, rarely preserved Variscan garnet-sillimanite-biotite-ilmenite-plagioclase-quartz (+/- K-feldspar Si-poor white mica) assemblages formed under amphibolite-facies subsolidus conditions (650 +/- 60 degrees C, 4.0 +/- 0.5 kbar). During subsequent decompression and cooling to greenschist-facies conditions garnet was replaced by biotite-sillimanite and later by white mica-chlorite intergrowths. Retrogression of Variscan biotite is evidenced by the exsolution of ilmenite along grain boundaries and cleavages, textures that were subsequently overgrown by Alpine garnet coexisting with Si-rich white mica, rare chloritoid (in metapelites), and hornblende (in metagreywackes). Alpine garnet shows prograde zoning and is Ca-rich, and thus is distinct from unzoned and Ca-poor Variscan garnet porphyroblasts. Estimated conditions (520 +/- 40 degrees C, 8.0 +/- 1.0 kbar) record elevated pressures during Alpine lower amphibolite-facies metamorphism. In the lowermost Bagni nappe, rare prograde-zoned, Ca-rich garnet in strongly retrogressed mylonitic quartz-phyllites allows isopleth thermobarometry, which indicates lower amphibolite-facies conditions (555 +/- 10 degrees C, 7.4 +/- 0.3 kbar) resembling those for Alpine garnet growth in the Castagna nappe. The similar clockwise P-T paths for prograde Alpine metamorphism and the consistent peak pressures of 7-9 kbar in the Castagna and Bagni nappes point to a joint short-lived metamorphism during overthrusting of the crustal-scale Serre nappe within the south European margin during the north-directed subduction of the Alpine Tethys. South-directed overthrusting of the now tilted Variscan crustal section of the Serre along the up to 500 m thick mylonite horizon of the Curinga-Girifalco Line is in agreement with seismic data indicating an extended, few kilometres thick low-velocity zone (Bagni and Castagna nappes and mylonites of the Curinga-Girifalco Line) below the exposed lower crustal section of the Serre nappe.
CRIS-Team WoS Importer:2021-05-14

Paleoproterozoic (2.01 Ga) high-pressure granulite facies metamorphism and isothermal decompression of garnet-orthopyroxene-cordierite-orthoamphibole gneisses from the Central Zone of the Limpopo Belt in eastern Botswana - Brandt, Sönke; Klemd, Reiner; Ramos, Joshua; Drueppel, Kirsten; Xie, Hanqiang (Lithos, 2023)
The Central Zone (CZ) of the Limpopo Belt in southern Africa is a complex high-grade metamorphic zone that experienced a, in part, poorly understood poly-metamorphic history. To address this, we present petrological and SHRIMP U-Pb zircon age data for samples of a garnet-and orthopyroxene-bearing cordierite-orthoamphibole (Grt-Opx-Crd-Oam) paragneiss and a charnockite from the Baines Drift and the Phikwe Complexes, respectively. The two complexes are the north-western segments of the CZ in which the metamorphic history is poorly con-strained. High-pressure (HP) granulite facies metamorphism and a clockwise P-T evolution for the feldspar-free Grt-Opx-Crd-Oam gneiss of the Baines Drift Complex are constrained by the application of pseudosection modelling, Grt-Opx thermometry, and quartz in-garnet (QinG) elastic barometry. Our results show that the peak-metamorphic garnet-orthopyroxene-rutile-ilmenite-quartz assemblage formed at HP granulite facies conditions of >900 degrees C and 14 kbar, followed by significant decompression at granulite facies conditions, as recorded by conspicuous orthopyroxene-cordierite coronas around garnet. The widespread formation of orthoamphibole documents subsequent near-isobaric cooling into the amphibolite facies. Based on the formation of metamorphic zircon in the Grt-Opx-Crd-Oam gneiss we precisely determined an age of 2014 +/- 8 Ma for HP granulite facies metamorphism in the Baines Drift Complex. Rare detrital zircons document a possible deposition of the sedi-mentary protolith later than ca. 2.55 Ga, as part of a poorly documented Paleoproterozoic sediment sequence of the Central Zone. The clockwise P-T path and the age of HP granulite facies metamorphism in the Baines Drift Complex as constrained here, are consistent with constraints from 2.02 Ga metamorphism in the Beit Bridge Complex, the major segment of the CZ. The HP metamorphism is interpreted to reflect intracontinental Paleo-proterozoic transpressional orogeny within the consolidated Kaapvaal-Zimbabwe Craton. The association of lower-crustal HP granulite facies rocks of the Baines Drift Complex next to mid-crustal upper-amphibolite facies rocks of the Phikwe Complex may reflect progress of nappe tectonics during the Paleoproterozoic orogeny. SHRIMP U-Pb zircon data indicate that the granite protolith of the charnockite from the Phikwe Complex intruded at 2586 +/- 27 Ma, broadly synchronously with major granitoid emplacement in the Beit Bridge Com-plex. The similar P-T evolution of ca. 2.02 Ga metamorphism and comparable voluminous granite emplacement at ca. 2.6 Ga indicate a common evolution of the Baines Drift, the Phikwe and the Beit Bridge Complexes in the CZ of the Limpopo Belt.
CRIS-Team WoS Importer:2023-03-03

Petrology and geochronology of a suite of meta-supracrustal rocks from Madukkarai, Tamil Nadu: Implications for the Ediacaran-Cambrian orogenesis of the Granulite Terrane of South India - Roy Choudhury, Sirina; Dey, Anindita; Brandt, Sönke; Sanyal, Sanjoy; Sengupta, Pulak (Lithos, 2021)
The Granulite Terrane of South India (GTSI) has two major components. An orthogneiss dominated northern block of Archaean/early Palaeoproterozoic age and an Ediacaran-Cambrian, high to ultra-high temperature meta-supracrustal dominated southern block (the Madurai Block, MB). It is commonly perceived that the two blocks of GTSI came into juxtaposition along the Palghat-Cauvery Shear/Suture Zone (PCSZ) during a continent-continent collision. However, the timing and the nature of the contact relations between the two major components remains controversial. In this work, detail petrological and geochronological study of two metapelites along with a meta-psammite (only for geochronological study), from the Madukkarai Supracrustal Unit (MSU) within the PCSZ, are presented. The studied metapelites show two distinct assemblages: A. Garnet + biotite + sillimanite (both idioblasts and pseudomorphs after kyanite) + K-feldspar + plagioclase + quartz + ilmenite (rutile, zircon and monazite as accessory phases). B. Mineralogy is similar to A but contains cordierite and minor spinel, but no zircon. Both the metapelites develop a gneissic fabric that is defined by centimetre thick laterally discontinuous garnet-bearing leucosomes. ‘Frozen in’ reaction textures, phase equilibria modelling and mineralogical thermobarometry yielded “peak” temperature and pressure of metamorphism in the range of 730–790 °C, 5.5–7 kbar (considering sillimanite and ilmenite to be stable). Subsequently, the rocks followed a decompressive retrograde P-T path recorded till 630 °C and 4 kbar. The geometry of the construed retrograde P-T path is similar to that commonly found in rocks of a continent-continent collision zone. LA-ICP-MS U[sbnd]Pb zircon dating and U-Th-total Pb monazite dating constrain the major high-grade metamorphism and deformation during 550–520 Ma with vestiges of 600 Ma old tectonothermal/ thermal event. The geological history of the MSU shares many characteristics with the Ediacaran-Cambrian meta-supracrustal rocks lying on both sides of the PCSZ, in terms of lithological association, timing of protolith formation, deformation and metamorphism. The variation in intensity of metamorphism in the meta-supracrustal rocks of the GTSI could be linked to differential upliftment of the GTSI during the neotectonic activities, followed by erosion. Integrating all the geological, geochronological and geophysical information, it has been argued that the GTSI behaved as a coherent continental block that was involved in continent-continent collision during the formation of the Ediacaran-Cambrian supercontinent Gondwanaland. The findings of this study do not corroborate the view that PCSZ is an Ediacaran-Cambrian terrane boundary.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Gondwanaland supercontinent; Granulite Terrane of South India; Palghat Cauvery Shear Zone; Phase equilibria modelling; Th–U–total Pb monazite dating; U-Pb zircon dating

Polyphase growth history of peritectic garnet from a granite: Trace-element zonation, Lu-Hf ages and their significance for the duration of granite-forming processes - Jung, S.; Pfänder, J. A.; Mezger, K.; Hellebrand, E.; Brandt, Sönke (Lithos, 2022)
Determining the ages and duration of high-grade metamorphic episodes during orogenesis and concomitant melt extraction events is pivotal in reconstructing and quantifying the chemical and petrological evolution of the Earth's continental crust over time. Major and trace elements combined with multichronometric garnet data from the Pan-African Damara belt of Namibia place absolute time constraints on high-grade regional metamorphism and melting in the lower crust that led to the production of widespread granites emplaced in the upper crust. Some of these granites contain inherited peritectic garnet with inferred igneous rims that record their genesis and evolution from formation by partially melting in the deep crust to the emplacement of their host rock at shallower levels. Particular characteristics of these garnets are textural and chemical disequilibrium features such as resorption, local development of partly euhedral crystal faces and occurrence of quartz-feldspar stringers in the rim of the garnet and trace element abundances with sharp concentration gradients. These features document a previous melting event followed by garnet crystallization in an ascending melt. With the exception of the outermost rim, which records late-stage diffusional features, the garnet crystals have constant Mg and Mn concentrations. In contrast, Ca shows pronounced chemical zoning. Trace elements (HREE, LREE, Zr, Sr, Y) are depleted in the core and enriched in the rim region indicating disequilibrium conditions during garnet growth. A pseudosection calculated with the garnet rim composition and the composition of the host granite yields P-T conditions of 0.62 GPa and 760 °C for the formation of the rim. This result is consistent with a P-T estimate of 0.68 GPa and 760 °C derived from the conventional garnet-biotite thermobarometer. Regional metamorphic conditions were above the cordierite-andalusite stability field with estimated conditions of 550-600 °C and 0.4–0.5 GPa. This P-T regime indicates that the garnet originally crystallized at deep crustal levels. Diffusion modelling suggests that the observed concentration gradient of Sm in garnet is consistent with a maximum duration of ca. 0.5–1.5 Ma for the inferred melting interval during peak metamorphism in the lower crust. High-precision multi-point Lu-Hf garnet-whole rock data yield dates of 522.0 ± 1.0 and 522.3 ± 0.9 Ma for two samples. Because of presumed short intervals between melting in the lower crust and intrusion of the granite, these dates are interpreted as the age of the melting event during high-grade metamorphism and are temporally indistinguishable from the crystallization interval. Thus, dehydration melting in the deeper crust during peak metamorphism produced peritectic garnet that was incorporated into the granitic melt followed by subsequent new growth of igneous garnet around peritectic cores during intrusion. Previously obtained Sm-Nd garnet whole rock ages are 20–25 Ma younger and likely represent cooling ages. This study shows that granites enriched in mafic components such as garnet and biotite may intrude as mixtures of melt and the peritectic assemblage produced by incongruent melting involving dehydration-melting of biotite in the lower crust. Melting episodes represent short-lived processes relative to the absolute duration of orogenic cycles.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Damara orogen; Lu-Hf garnet dating; Peritectic garnet; Pseudosection modelling; Trace element garnet

Pressure-temperature evolution during two granulite-facies metamorphic events (2.62 and 2.02 Ga) in rocks from the Central Zone of the Limpopo Belt, South Africa - Brandt, Sönke; Klemd, Reiner; Li, Qiuli; Kröner, Alfred; Brandl, Guenther; Fischer, Andreas; Bobek, Patrick; Zhou, Tian (Precambrian Research, 2018)
The Central Zone of the Limpopo Belt in southern Africa is a classical example of a polymetamorphic terrane that experienced three metamorphic events at 3.22 Ga (M1), 2.66–2.61 Ga (M2) and 2.02 (M3). However, the geodynamic significance of these events is controversial as their P-T evolution was poorly constrained. We present new petrological and geochronological data for the M2 and M3 events. The Neoarchean M2 event is well-preserved in samples from a newly discovered enclave of supracrustal and magmatic rocks in the 2.612 Ga Bulai pluton that shielded the enclave against a Paleoproterozoic M3 overprint, which is dominant in rocks exposed outside the pluton. P-T pseudosection modelling for migmatitic Grt-Crd metapelites from the enclave and the rock sequence outside the pluton indicates an opposite metamorphic evolution, a counterclockwise P-T path for M2 but a clockwise path for M3. Spinel-quartz assemblages in the enclave metapelites record early heating to UHT conditions (ca. 930 °C, 5.5 kbar) at intermediate crustal levels. The peak-pressure M2-assemblage garnet-cordierite-sillimanite-K-feldspar-plagioclase-quartz ± rutile formed at ca. 860 °C and 7.5 kbar during a moderate pressure increase. Cordierite coronas around garnet record subsequent decompression. We interpret the counterclockwise P-T evolution during M2 to result from convergence of the Zimbabwe and Kaapvaal Cratons, which has led to subduction of oceanic lithosphere beneath the Zimbabwe Craton. Subsequent slab retreat has caused asthenosphere upwelling, thereby inducing delamination of the lithospheric mantle. Intrusion of hot asthenospheric material beneath the crust induced early UHT metamorphism at mid-crustal levels. The subsequent moderate pressure increase was related to the ensuing collision of the cratons. Post-peak decompression records incorporation of the enclave into the Bulai pluton melt and uplift in the ascending granitoid melt. The peak M3-assemblage garnet-cordierite-sillimanite-K-feldspar-rutile-plagioclase-quartz formed in metapelites occurring outside the pluton during near-UHT conditions (ca. 880 °C, 7.5 kbar). Cordierite coronas around garnet record subsequent decompression. New growth of garnet and sillimanite at the expense of cordierite documents late near-isobaric cooling to <700 °C. The resulting clockwise P-T path for M3 granulite-facies metamorphism is interpreted to record an intracontinental Paleoproterozoic transpressional orogeny within the consolidated Kaapvaal-Zimbabwe Craton, which was induced by far-field tectonic processe
Keywords: Limpopo Belt; Pseudosection; P-T path; Granulite; Neoarchean; Delamination

Timing and duration of discrete tectono-metamorphic events of the polymetamorphic high-grade Central zone of the Limpopo Belt (South Africa): Insight from in situ geochronology of monazite and zircon - Zhou, Tian; Klemd, Reiner; Brandt, Sönke; Liu, Yu; Li, Qiu Li (Precambrian Research, 2022)
The Central Zone of the Limpopo Belt in southern Africa is a complex polymetamorphic terrane that has experienced three metamorphic events, at 3.22 Ga (M1), 2.71–2.56 Ga (M2) and 2.02 Ga (M3). On the basis of a previous detailed petrological and geothermobarometrical study of a newly discovered supracrustal enclave within the Bulai Pluton (ca. 2.61 Ga granitoid gneiss in the Central Zone), we conducted a geochronological in situ study of texturally and chemically different monazite and zircon grains, which occur respectively as inclusions in garnet, in decompressional cordierite coronas around garnet and as matrix grains in polymetamorphic granulite-facies metapelites. Secondary-ion mass spectrometry (SIMS) in situ analyses of the monazite and zircon grains in thin sections, complemented by analyses of separated zircon grains, allowed the texturally-controlled direct determination of U-Pb and 207Pb/206Pb ages at a scale of < 10 μm. A concordant age of ca. 2.71 Ga derived from zircon included in garnet is interpreted to reflect the age of initial garnet growth during the prograde M2 metamorphism. Zircons in the cordierite coronas around garnet revealed a slightly younger concordant age of ca. 2.56 Ga. Zircon growth in the coronas is related to the retrograde breakdown of garnet (Zr-bearing) through to the decompression reaction garnet + sillimanite + quartz → cordierite + zircon and hence the ca. 2.56 Ga zircon age is interpreted to reflect the timing of post-peak decompressional uplift. The zircon ages constrain the duration of M2 metamorphism to approximately 145 Myr. A concordant 2.71 Ga age of large monazite inclusions in garnet cores corroborates the 2.71 Ga zircon age of initial garnet growth during the prograde M2 metamorphism. Core domains of the largest monazite in cordierite corona revealed ages between 2.5 and 2.0 Ga that are interpreted to reflect (multiple) Pb-loss during the M3 granulite-facies metamorphism. Other monazites in cordierite coronas and matrix showed an age of ca. 2.0 Ga, reflecting complete re-equilibration or new growth during M3 overprinting. Owing to the preservation of the original micro-textures related to the growth of zircon and monazite we were able to link the age data with the P-T record, and refine the timing and duration of the M2 granulite-facies metamorphism (approximately 2.71–2.56 Ga) in the Limpopo Belt that was previously dated at ca. 2.62 Ga by zircon separation techniques. The ca. 145 Ma duration of granulite-facies metamorphism is consistent with a tectonic model of long-lasting asthenosphere upwelling and subsequent continent–continent collision in the late Neoarchean. Decompression triggered by post-collisional extension occurred at 2.56 Ga. Paleoproterozoic M3 granulite-facies metamorphism at ca. 2.0 Ga caused the widespread re-setting of the U-Pb and Pb-Pb data that also affected most zircon and monazite grains. This study reveals that precise dating of the timing and duration of distinct tectono-metamorphic events by texturally-controlled in situ geochronology allows a much better insight into the complex geodynamic evolution of high-grade polymetamorphic terranes.
CRIS-Team Scopus Importer:2022-01-21
Keywords: Duration of metamorphic events; Limpopo Belt; Monazite; Polymetamorphism; Secondary ion mass spectrometry; U-Pb dating; Zircon

Unravelling the P-T-t history of three high-grade metamorphic events in the Epupa Complex, NW Namibia: Implications for the paleoproterozoic to mesoproterozoic evolution of the Congo Craton - Brandt, Sönke; Klemd, Reiner; Xie, Hanqiang; Bobek, Patrick (American Journal of Science, 2021)
The Epupa Complex of northern Namibia constitutes the south-western margin of the Archean Congo Craton of central Africa. We present new petrological and geochronological data for metasedimentary migmatites that decode the poorly-known Paleoproterozoic to Mesoproterozoic evolution of this remote part of the craton. Detrital magmatic zircons with concordant 207Pb/206Pb ages between 1898 and 1774 Ma are interpreted to demonstrate the formation of the metasedimentary protoliths through reworking of Paleoproterozoic granitoids of a magmatic arc in a back-arc basin. SHRIMP U-Pb zircon analyses of metamorphic rims around the detrital grains linked with constraints from pseudosection modelling revealed three distinct high-grade metamorphic events in the migmatites. Late Paleoproterozoic regional HT-LP metamorphism between 1740 and 1720 Ma constitutes the oldest event and only affected the rocks of the northernmost part of the Epupa Complex (Eyao Unit). Heating to mid-amphibolite facies peak P-T conditions of 720 °C and 4 kbar caused the partial replacement of early biotite-sillimanite by garnet-cordierite assemblages during melt-producing reactions in metapelites. The near-isobaric heating-cooling P-T paths and the high geothermal gradient (60 °C/km) are consistent with HP-LP metamorphism in a back-arc basin setting with up-rising basic melt as heat source. Early Mesoproterozoic (1530 Ma) HT-LP metamorphism is recorded by rare Mg-rich Opx-Crd rocks that are restricted to the westernmost part of the Eyao Unit. Near-isobaric P-T paths culminate at granulite facies peak-conditions of 830 °C and 2 kbar. This local HP-LP event is interpreted to record contact metamorphism related to the coeval emplacement of early-Mesoproterozoic granitoids or the emplacement of intimately associated gabbros. Metapelitic Grt-Bt-Sil migmatites record the third high-grade metamorphic event that was active at ca. 1330 Ma and is restricted to the southern part of the Epupa Complex (Orue Unit). Sillimanite pseudomorphs after kyanite and late cordierite coronas around garnet indicate a clockwise P-T path during regional upper-amphibolite facies metamorphism that peaks at lower crustal conditions of 770 °C and 7.5 kbar. The clockwise P-T path is interpreted to reflect crustal thickening through magmatic accretion of basic melts that produced the coeval Kunene Intrusive Complex, the largest massif-type anorthosite in the world. The metamorphic events detected in the migmatites record a change of the geotectonic position of the Epupa Complex from a convergent continental margin during the late Paleoproterozoic to an intracratonic position in the Mesoproterozoic. The migmatites of the Eyao Unit were affected by an intense hydrothermal alteration during the Pan-African orogeny (ca. 520 Ma) that also caused the partial re-setting of the U-Pb zircon isotope system.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Amphibolite facies; Congo Craton; Epupa Complex; HT-LP metamorphism; Migmatite; P-T-t path; Paleoproterozoic; Pseudosections